Modeling and control of wind power generation system based on MMC-PET interface during grid faults - CHENG Qiming; SUN Yinghao; CHENG Yinman; ZHANG Lei; QU Bogang (电力工程技术)
In recent years, the power electronic transformer (PET) used as the wind energy conversion system at the grid interface has attracted widespread attention for its ability to effectively suppress voltage fluctuations caused by the transient characteristics of wind energy without the need for additional reactive compensation devices. However, the conventional PET structure poses control challenges during grid faults, making it difficult to manage unbalanced grid conditions and compromising system dynamic performance. To enhance dynamic performance and fault tolerance, this paper proposes a novel wind energy conversion system based on the modular multilevel converter (MMC) power electronic transformer, along with its structural design and control strategy. Firstly, a fault-switching control strategy based on passive sliding mode control is designed to handle system operation during faults, incorporating sub-modules with fault protection features to dissipate fault power. Secondly, extensive simulation studies are conducted under various operating conditions using software simulation and semi-physical simulation platforms. Finally, comparative experiments between the proposed wind power generation system and traditional wind power systems validate the advantages of the novel system structure using the proposed control strategy, including reactive power compensation, effective limitation of submodule voltage rise during faults, and improvement in power quality. The results demonstrate the outstanding fault crossing capabilities of the proposed system in meeting the latest requirements for grid operation under fault conditions.